The Effect of a Higher Bias Gas Flow on Imposed T-Piece Resistance and Breathing in Preterm Infants at Birth - Kuypers, Kristel L. A. M.; Willemsen, Lieve A.; Cramer, Sophie J. E.; Kashyap, Aidan J.; Drevhammar, Thomas; Hooper, Stuart B.; te Pas, Arjan B. (Frontiers in Pediatrics, 2022)
Objective The resistance created by the PEEP-valve of a T-piece resuscitator is bias gas flow dependent and might affect breathing in preterm infants. In this study we investigated the effect of a higher bias gas flow on the imposed inspiratory and expiratory T-piece resistance and expiratory breaking manoeuvres (EBM) in preterm infants during spontaneous breathing on CPAP at birth. Methods In a retrospective pre-post implementation study of preterm infants <32 weeks gestation, who were stabilised with a T-piece resuscitator, a bias gas flow of 12 L/min was compared to 8 L/min. All spontaneous breaths on CPAP within the first 10 min of starting respiratory support were analysed on a breath-by-breath basis to determine the breathing pattern of each breath and to calculate the imposed inspiratory and expiratory T-piece resistance (Ri, Re), flow rates and tidal volume. Results In total, 54 infants were included (bias gas flow 12 L/min: n = 27, 8 L/min: n = 27) with a median GA of 29+6 (28+4–30+3) and 28+5 (25+6–30+3), respectively (p = 0.182). Ri and Re were significantly lower in the 12 L/min compared to 8 L/min bias flow group [Ri: 29.6 (26.1–33.6) vs. 46.4 (43.0–54.1) cm H2O/L/s, p < 0.001; Re: 32.0 (30.0–35.1) vs. 48.0 (46.3–53.9) cm H2O/L/s, p < 0.001], while the incidence of EBM [77% (53–88) vs. 77% (58–90), p = 0.586] was similar. Conclusion During stabilisation of preterm infants at birth with a T-piece resuscitator, the use of a higher bias gas flow reduced both the imposed inspiratory and expiratory T-piece resistance for the infant, but this did not influence the incidence of EBMs.